Neem decline in West Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Throughout the semi-arid regions of West Africa the neem tree (Azadirachta indica) is used wifely for planting in shelterbelts and windbreaks to halt or reduce soil losses. The hardiness and versatility of the neem has enabled the tree to play an...